The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.30599/jipfri.v6i1.1255
|View full text |Cite
|
Sign up to set email alerts
|

Study of Critical Thinking Skills for Junior High School Students In the Era Industial Revolution 4.0

Abstract: The background of the research is that skills are needed in accordance with the era of the industrial revolution 4.0, especially in the 21st century, namely critical thinking skills. For this reason, research is needed to determine the description of critical thinking skills. This research is a preliminary study that aims to describe the ability of critical thinking skills in learning science physics. Descriptive research method using google form. The research subjects were 33 students of SMP Negeri 59 Palemba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…According to research conducted by Cynthia et al (2023), it was found that the product developed had a practitioner assessment percentage of < 80%, so the emodule was included in the practical category and also met the eligibility criteria (valid) so that e-module teaching materials are important. The learning process used e-module also can make student has the critical thinking ability (Azmi et al, 2021;Azmi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…According to research conducted by Cynthia et al (2023), it was found that the product developed had a practitioner assessment percentage of < 80%, so the emodule was included in the practical category and also met the eligibility criteria (valid) so that e-module teaching materials are important. The learning process used e-module also can make student has the critical thinking ability (Azmi et al, 2021;Azmi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Pembelajaran IPA di sekolah mampu meningkatkan pola berpikir siswa, namun belum mampu memaksimalkan keterampilan berpikirnya dikarenakan proses pembelajaran berpusat pada guru (Purwati et al, 2019). Ketidakmampuan siswa mengaitkan materi yang dipelajari menjadi indikasi bahwa keterampilan berpikir kritisnya masih rendah (Azmi et al, 2022). (Khasani et al, 2018) menemukan bahwa tingkat kemampuan berpikir kritis siswa di kelas VIII-A SMPN 4 Belik pada materi Hukum Newton ternyata masih rendah (rerata skor 49,29), dikarenakan kurangnya variasi metode dan model pembelajaran, minat dan motivasi siswa, fasilitas laboratorium dan sumber belajar materi Hukum Newton.…”
Section: Pendahuluanunclassified